Increasing the Use of Learning Methods in Encouraging Student Literacy Through Combination Methods in Class V of Langawai Elementary School, Palue District, Sikka Regency” - Heronimus Lanbertus Da Costa (PT FORMOSA CENDEKIA GLOBAL, 2023)
Conduct consultations with leaders or mentors regarding the design of actualization activities, create literacy corners and reading trees with students in class, carry out literacy movement activities 15 minutes before starting learning and guide students to retell reading content that has been read and understood, carry out visit activities to school library, carry out additional hours of study activities for students who are not able to read quickly, carry out evaluations of actualization activities, compile reports on actualization activities, increase the basic skills of prospective civil servants